Analisis Hambatan Belajar Mahasiswa dalam Perkalian Pecahan: Sebuah Studi Hermeneutics Phenomenology di Perguruan Tinggi - Isnawan, Muhamad Galang; Alsulami, Naif Mastoor; Rusmayadi, Muh.; Samsuriadi, Samsuriadi; Sudirman, Sudirman; Yanuarto, Wanda Nugroho (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Multiplication of fractions is one of the operations on fractions that tends to be easy, but it becomes a problem for students. Only a little previous research has examined the multiplication of fractions and the factors that cause this problem at the tertiary level. This study aims to describe the factors that cause problems in terms of the types of learning barriers that students experience. The research design is hermeneutics phenomenology. The participants in this study were 15 students aged 18-25 years, 7 boys and 8 girls, 9 students majoring in natural sciences during high school, and 6 students from social studies majors. The researcher is the main instrument, with a fraction multiplication test consisting of 2 questions developed by NCTM and a semi-structured interview guide as an additional instrument. Data is processed using NVivo-12-assisted thematic analysis to simplify the coding process. The study revealed that students experienced more learning difficulties when working on non-routine fraction multiplication problems. For routine problems, students experience learning difficulties with the type of ontogenic obstacle that is psychological (not careful). For non-routine problems, students experience learning barriers with epistemological types because they rarely work on word problems, as well as ontogenic obstacles that are conceptual and psychological.